2010
DOI: 10.1097/pts.0b013e3181ddfcd0
|View full text |Cite
|
Sign up to set email alerts
|

Parents' Perceptions of Medical Errors

Abstract: Perceived medical errors can impact both the patient and the family in many ways. We recommend that providers acknowledge the full impact of a perceived error and tailor their response to meet the specific needs of the patient and family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(74 citation statements)
references
References 35 publications
2
65
0
1
Order By: Relevance
“…Are they right? Consistent with other research,5 the experiences of our participants do highlight the importance of tailoring institutional responses to individual patients' needs. That points away from using strict protocols—but does not mean guidelines should be abandoned.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Are they right? Consistent with other research,5 the experiences of our participants do highlight the importance of tailoring institutional responses to individual patients' needs. That points away from using strict protocols—but does not mean guidelines should be abandoned.…”
Section: Discussionsupporting
confidence: 89%
“…Existing literature about injured patients' needs establishes some fundamentals: patients and families5 value efforts to prevent recurrences3 6 and disclosure communications that are honest, transparent, efficient and compassionate 3 7–9. Their accounts reveal that patient safety incidents often involve immense emotional, physical and financial impacts,10 which can be exacerbated by poor responses from providers 11 12…”
Section: Introductionmentioning
confidence: 99%
“…Studies of patients’ actual experiences with disclosure of adverse events provide important insights that significantly extend the findings of these earlier studies, and also help to define what patients want after an event has occurred 17 ,18,21, 22 . First, patient interviews confirm that disclosure often does not occur.…”
Section: Introductionmentioning
confidence: 71%
“…17 A few adult studies have found that patients identify numerous verified errors and AEs not otherwise documented in the medical record. [18][19][20] Pediatric data on patient and family involvement in error and AE detection are limited [21][22][23][24] but similarly suggest that families often report verified errors and AEs that are not detected through other sources. 23 Given the family's central role in pediatrics, parent-reported errors may be a fruitful source of error and AE surveillance for hospitalized children and may provide lessons regarding the utility of family error reporting in other populations.…”
Section: Main Outcomes and Measures-medical Errors And Preventable Aesmentioning
confidence: 99%